Aging, proximity to death, and religiousness - Marie Lechler; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
Considerable evidence has documented that the elderly are more religious and that religiousness is associated with better health and lower mortality. Yet, little is known about the reverse role of life expectancy or proximity to death, as opposed to age, for religiousness. This paper provides evidence for the distinct role of expected remaining life years for the importance of religion in individuals' lives. We combine individual survey response data for more than 311,000 individuals from 95 countries over the period 1994-2014 with information from period life tables. Contrary to wide-held beliefs, religiousness decreases with greater expected proximity to death. The findings have important implications regarding the consequences of population aging for religiousness and associated outcomes.
Keywords: J10; N30; Z12; 330; Religiousness; demographics; proximity of death; remaining life years